Career challenges at Media Inc. Issue 1 (13th May 2019) - Barnardo, Claire; Ronnie, Linda
Abstract : Learning outcomes: The learning objectives to be drawn from the case are as follows: to explore the violation of the psychological contract; to understand the notion of the boundaryless career; to assess the advantages and disadvantages of leaving an employer; to explore the factors to be considered when contemplating a career move; and to identify career management strategies in the digital age. Case overview/synopsis: Management practices at Media Inc. have resulted in a growing sense of dissatisfaction for Palesa Khume who had been hired to head up the management team of a new glossy women's magazine, Mirror Me. This project was exciting and exhilarating for Khume. The shifting of agreed-upon objectives causes increased stress to Media Inc. employees and comes to a head with the reneging of the agreed-upon year-end bonus to Khume. She is now faced with the decision whether she should stay or leave the organisation. Complexity academic level: Postgraduate Business students, especially MBA students. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 6: Human Resource Management